Familial gastric cancer: genetic susceptibility, pathology, and implications for management. Issue 2 (February 2015) - Oliveira, Carla; Pinheiro, Hugo; Figueiredo, Joana; Seruca, Raquel; Carneiro, Fátima
Summary Familial gastric cancer comprises at least three major syndromes: hereditary diffuse gastric cancer, gastric adenocarcinoma and proximal polyposis of the stomach, and familial intestinal gastric cancer. The risk of development of gastric cancer is high in families affected b-y these syndromes, but only hereditary diffuse gastric cancer is genetically explained (caused by germline alterations of CDH1, which encodes E-cadherin). Gastric cancer is also associated with a range of several cancer-associated syndromes with known genetic causes, such as Lynch, Li-Fraumeni, Peutz-Jeghers, hereditary breast–ovarian cancer syndromes, familial adenomatous polyposis, and juvenile polyposis. We present contemporary knowledge on the genetics, pathogenesis, and clinical features of familial gastric cancer, and discuss research and technological developments, which together are expected to open avenues for new genetic testing approaches and novel therapeutic strategies.